Concept of Pesantren Management in Developing Muslim Personal - Rusnila Hamid (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
Management is important in pesantren because to run optimally a pesantren, the development of pesantren, and for the advancement of the pesantren. Pesantren whose management system is low or even not good, can result in reduced the usefulness of a pesantren, so that good management is needed in managing Pesantren in order to print a true Muslimgeneration. Religious guidance actually has a function and purpose. Religious guidance is carried out with the aim of helping individuals understand their potential, adjust to the environment, find solutions to the problems faced in order to achieve well-being in life. Religious guidance has a preventive function that helps individuals maintain or prevent the onset of problems forthemselves.